3

A = {0,1, a}

0 1 a 0 0 1 a 1 1 1 1 a a 1 a

.1

* 0 1 a

0 0 0 0

1 0 1 a

a 0 a a

x x

0 1

1 0

a a

: :

: . ( .a∨a = a∨a = a ) -

a=a
.

, a ∨ a =1

:

4-

.2

:

zw + xyw '

?

w⊕ x
:

f = x ' zw '+ xy + x ' z ' w '

:

( xyw '+ x ' y ' z '+ x ' yzw) ⊕ ( x ' y + y ' w ') =

: : : .3

f ( x, y, z ) = xy + xyz + yz f ( x, y , z ) = xy + xyz + yz = xy ( z + z ) + xyz + yz ( x + x ) = xyz + xy z + x yz + x yz

: NPN-equivalence : ,f ,g :NPN equivalent ,f f,g ( ( )f ) . : 2NPN .1 .2 .3

:

3-

NPN class

:NPN . .class . . :2007 :NPN . , . . , , . . . .4

f1 = bd '+ a ' bc + abc ' f 2 = a ' c '+ bc ' d ' f 3 = c + adc '+ b ' ad ' f 4 = c + bda + b ' ad '

:

NPN class

f 2 , f3 .NPN class

f1 , f 4

: "

.5

:

F = ab c + abd + bc d
. (negation)

?

"

(15%) (

ϕ1 = xyz + x yv + yz v ϕ2 = xy + xv + zv + zy ϕ4 = yzv + x zv + xyzv + x y zv
:

ϕ3 = xv + zv + zy + x v

? -

"

(15%) (

ϕ1 = xyz + x yv + yz v
-

ϕ2 = xy + xv + zv + zy ,
ϕ3 = xv + zv + zy + x v

-

ϕ4 = yzv + x zv + xyzv + x y zv
, ( 1, 2, 3, 4 )

( x, y, z,v )
.

(10%) (

ϕ2 = x y + xv + zv + zy
1) 2)

y

ϕ2 ϕ2

z

x
y

ϕ2

x

z

v

ϕ2

ϕ 4 = yzv + x zv + xyz v + x y z v =
= yzv + xyz + x y v
1) 2)

z
x
y

ϕ4 ϕ4

y

ϕ4

x
z

ϕ4

:

:Xor form : x 0 0 1 1 y 0 1 0 1

.6

x⊕ y
0 1 1 0

1⊕1 = 0 x⊕0 = x x ⊕1 = x x⊕x =0 x ⊕ x =1 x0 ⊕ x1 = x0 ⊕ x1 x ⊕ ( y ⊕ z ) = ( y ⊕ x) ⊕ z

x0 ~ x1 = x0 x1 + x0 x1 x~0=x x ~1= x x ~ x =1 x~ x=0 x0 ~ x1 = x0 ~ x1 = x ⊕ y
x + y = x ⊕ y ⊕ xy .

x ( y ⊕ z ) = xy ⊕ xz .

x0 | x1 ∨ x0 ~ x1 = = x0 x1 ∨ x0 ⊕ x1 = = ( x0 x1 ⊕ 1) ∨ ( x0 ⊕ x1 ⊕ 1) = x0 x1 ⊕ 1 ⊕ x0 ⊕ x1 ⊕ 1 ⊕ ( x0 x1 ⊕ 1)( x0 ⊕ x1 ⊕ 1) = x0 x1 ⊕ x0 ⊕ x1 ⊕ ( x0 x1 ⊕ 1)( x0 ⊕ x1 ⊕ 1) = x0 x1 ⊕ x0 ⊕ x1 ⊕ x0 x1 ⊕ x0 x1 ⊕ x0 x1 ⊕ x0 ⊕ x1 ⊕ 1 = 0 ⊕ 1 = 1
.

:XOR (SOP) .XOR +

x + y = x ⊕ y ⊕ xy

. .

x ⊕1 = x .

: : x 0 0 1 1 y 0 1 0 1

.2

x→ y
1 1 0 1

x0 → x1 = x0 + x1 x→0= x x →1=1 1→ x = x 0 → x =1 x→x=x x → x =1 x→x=x
x→ y= y→x .

y → x = y+ x = y+ x = x+ y = x→ y

x+ y = x→ y .

xy = x → y . xy = xy = x + y = x → y

:NOR :

.3

x↓ y = x+ y

x+ y = x+ y = x↓ y x=x↓x x1 x2 = x1 ↓ x2 x1 + x2 = x1 + ( x2 ↓ x2 ) = x1 ↓ ( x2 ↓ x2 ) = [ x1 ↓ ( x2 ↓ x2 )] ↓ [ x1 ↓ ( x2 ↓ x2 )]